ANALISIS SENTIMEN MASYARAKAT INDONESIA TERHADAP SEA GAMES 2023 DI TWITTER DENGAN METODE NAÏVE BAYES - Dewi Sekar Arum; Sufajar Butsianto; Retno Fitri Astuti (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2023)
This study aims to analyze the sentiment of Indonesian society towards SEA Games 2023 on the Twitter platform using the Naïve Bayes method. Data from Twitter users' responses related to SEA Games were collected and sentiment analysis was performed to identify positive, negative, and neutral responses. The analysis results showed that the majority of responses were positive (33.4%), followed by neutral responses (59.1%) and negative responses (7.5%). The Naïve Bayes method was used to classify sentiment by dividing the data into training and testing sets in different ratio comparisons. The performance of the algorithm was evaluated based on accuracy, precision, and recall. The testing results showed that the 40:60 ratio had the highest accuracy (92.70%). The most frequently occurring words in positive responses were "champion," "achieve," "national team," "gold," "medal," "win," "play," "already," "achievement," and "world." In negative responses, the most frequent words were "return," "incident," "lose," "ask," "fail," "minister of youth and sports," "opening," "until," "same," and "serious." Based on the analysis results, it is recommended that stakeholders leverage the positive sentiment to strengthen public support, conduct regular sentiment analysis, and further develop sentiment classification methods. This study provides insights into public perspectives on SEA Games 2023 and can serve as a basis for informed decision-making in the planning and execution of future sports events.